Kontribusi Nyai Nur Khodijah: Telaah Historis Perintis Feminisme Pesantren - Hamidah, Ani Mar’atul; Atik Masfiah (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Background.The founding figure of the Islamic boarding school is identical to the kiai. Even though it could be that the originator of this brilliant idea came from the figure of the nyai. Aim.This article will reveal and describe the forerunner of Islamic boarding school feminism through the figure of Nyai Nur Khodijah:the biography, tirakatan culture, and the history of Nyai’s struggle in pioneering women’s boarding schools even though women were marginalized at that time. Methods.The method used in this research isindividual life history with a qualitative approach. Results.The gait of Nyai Nur Khodijah with her husband, Kiai Bisri Syansuri in pioneering the Mamba’ul Ma’arif Denanyar Jombang Islamic Boarding School should be appreciated, especially women’s cottages. This Islamic boarding school always shows its existence in the world of Islamic education. In fact, now the curriculum has been transformed according to the times. In addition to focusing on Islamic science, female students are also equipped with knowledge about general skills to support their potential and provisions after graduation in society. His contribution succeeded in empowering female students so that women are seen as having dignity and are nevermore marginalized. The advice from Nyai Nur Khodijah who is able to motivate her female students, even women in general, is “Your tirakat, determines your husband's future”.